(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
In Bangladesh beetroot is getting attention in recent years due to its high food value and potential industrial use. The present study was conducted to assess the food value in terms of biochemical and mineral nutritional constituents of four exotic beetroot varieties (viz. Chioggia, Detroit Dark Red, Early Wonder Tall Top, and Red Ace) of Bangladesh. The pH, brix and dry matter (DM%) levels of the four beetroot varieties ranges between 5.52 to 6.51, 8.9 to 10.5, and 8.8 to 11.0%, respectively; and Detroit Dark Red had the highest DM%. the protein, fibre, ash, and total sugar contents were also significantly varied in the four varieties and the values ranged between 10.80-12.50, 5.10-6.20, 7.65-8.86, 2.62-6.06%DM, respectively. The vitamin C was found highest in Chioggia (6.20 mg/100g). Among the micro and macronutrient elements tested, all parameters were significantly varied and Detroit Dark Red contained the highest amount of N (1904 mg 100 g−1 DM), Fe (53 mg 100 g−1 DM), Zn (26 mg 100 g−1 DM) and Mn (17 mg 100 g−1 DM); while Chioggia contained the highest amount of K (3331 mg 100 g−1 DM), Ca (151 mg 100 g−1 DM) and B (21 mg 100 g−1 DM). Total anthocyanin and total phenolic contents also varied among the varieties and the highest values were observed in Chioggia and Early Wonder Tall Top, respectively. Based on the observed parameters, Chioggia and Detroit Dark Red seemed to be the better performers among the four beetroot cultivars. Vol. 9, No. 3, December 2022: 279-287